2015
DOI: 10.1038/srep08136
|View full text |Cite
|
Sign up to set email alerts
|

Dental plaque development on a hydroxyapatite disk in young adults observed by using a barcoded pyrosequencing approach

Abstract: Dental plaque is a dynamic microbial biofilm ecosystem that comprises hundreds of species including difficult-to-cultivate bacteria. We observed the assembly of a plaque bacterial community through 16S rRNA gene analysis. Plaque samples that accumulated on a hydroxyapatite disk for 1, 2, 3, 4, 5, and 7 days with saliva on day 0 were collected from 19 young adults using a removable resin splint. Quantitative PCR analysis showed that the total bacterial amount gradually increased and reached a plateau on day 4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 26 publications
(34 reference statements)
5
60
1
Order By: Relevance
“…1 It has previously been confirmed that there are substantial differences between planktonic bacteria and bacteria in biofilm and that biofilm has a more important role in oral health. 2,3 However, experiments with real oral biofilm are difficult because it is hard to control the human oral environment, and the oral microbiota of the biofilms of each human also exhibit substantial differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It has previously been confirmed that there are substantial differences between planktonic bacteria and bacteria in biofilm and that biofilm has a more important role in oral health. 2,3 However, experiments with real oral biofilm are difficult because it is hard to control the human oral environment, and the oral microbiota of the biofilms of each human also exhibit substantial differences.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, experiments with real oral biofilm are difficult because it is hard to control the human oral environment, and the oral microbiota of the biofilms of each human also exhibit substantial differences. 1 Therefore, an in vitro model that mimics real oral biofilm is needed to understand the complexities of biofilm. Microcosm biofilm models have been suggested to overcome such limitations, 4,5 and some researchers have reported that these in vitro models are similar to real oral biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that Capnocytophaga spp. increase their dominance within the bacterial community as dental plaque matures (57). Furthermore, a number of other bacteria, including major periodontal pathogens, have been found to harbor T9SS-related genes (28).…”
Section: Figmentioning
confidence: 99%
“…Temporal changes during supragingival plaque formation vary among individuals (15). Therefore, if a representative sample of plaque is required on one occasion, plaque maturity should be determined.…”
Section: What Is the Oral Microbiome?mentioning
confidence: 99%